Quantitative Color Doppler Ultrasonography Measurement of Thyroid Blood Flow in Patients with Graves’ Disease - Yuksekkaya, Ruken; Celikyay, Fatih; Gul, Serdar S.; Yuksekkaya, Mehmet; Kutluturk, Faruk; Ozmen, Cansel (Current Medical Imaging, 2020)
Background: Graves’ Disease is an autoimmune disorder characterized by increased levels of thyroid hormones correlated with increased thyroid blood flow. Thyroid scintigraphy is an important and conventional method. However, it has limited accessibility, has ionizing radiation, and is expensive. Objectives: To investigate the thyroid blood flow in patients with Graves’ Disease by color Doppler Ultrasonography and a newly developed software Color Quantification. Methods: Forty-one consecutive subjects with GD and 41 healthy controls were enrolled. Color Doppler ultrasonography parameters of the thyroid arteries and Color Quantification values of the gland were measured by a radiologist. The correlations between thyroid blood flow parameters, levels of 99m Technetium pertechnetate uptake, thyrotropin, and free thyroxine were evaluated. The diagnostic performances of these parameters were investigated. Results: The peak systolic-end diastolic velocities of thyroid arteries and Color Quantification values were increased in the study group (p < 0.05 for all). We observed negative correlations between thyrotropin levels and peak-systolic and end-diastolic velocities of superior thyroid arteries and Color Quantification values. There were positive correlations between 99m Technetium uptake levels and thyroid blood flow parameters (p < 0.05 for all). In the diagnostic performance of thyroid blood flow parameters, we observed utilities significantly in peak-systolic and end-diastolic velocities of thyroid arteries and Color Quantification values (p < 0.05 for all). Conclusion: The increased peak-systolic and end-diastolic velocities of thyroid arteries, and increased Color Quantification values might be helpful in the diagnosis of Graves’ Disease.
Keywords: Technetium (99mTc) pertechnetate thyroid scintigraphy